Estimating the environmental impacts of carbon emissions from fuel consumption during construction activities - Pezhman Shahid, 1984-, author; Khairulzan Yahya, supervisor; Fakulti Kejuruteraan Awam (2015)
Thesis (Sarjana Sains (Awam - Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2015